Micro-aeration: an attractive strategy to facilitate anaerobic digestion. Issue 5 (May 2023) - Fu, Shanfei; Lian, Shujuan; Angelidaki, Irini; Guo, Rongbo
Abstract: Micro-aeration can facilitate anaerobic digestion (AD) by regulating microbial communities and promoting the growth of facultative taxa, thereby increasing methane yield and stabilizing the AD process. Additionally, micro-aeration contributes to hydrogen sulfide stripping by oxidization to produce molecular sulfur or sulfuric acid. Although micro-aeration can positively affect AD, it must be strictly regulated to maintain an overall anaerobic environment that permits anaerobic microorganisms to thrive. Even so, obligate anaerobes, especially methanogens, could suffer from oxidative stress during micro-aeration. This review describes the applications of micro-aeration in AD and examines the cutting-edge advances in how methanogens survive under oxygen stress. Moreover, barriers and corresponding solutions are proposed to move micro-aeration technology closer to application at scale. Highlights: Micro-aeration represents a promising strategy to facilitate anaerobic digestion (AD), as it enhances hydrolysis, improves methane yield, oxidizes specific pollutants, and thereby overall improves AD. Low oxygen solubility in water, rapid consumption of dissolved oxygen by facultative microbes, the formation of microbial aggregates, and the intrinsic tolerance of some methanogenic species to oxygen are suggested as potential mechanisms for unimpaired AD process in response to oxygen exposure. Fundamental understanding of anaerobic microorganisms' tolerance to oxygen stress and long-term pilot scale tests of effects of micro-aeration on AD are needed in order to move micro-aeration technology closer to applications.